2001
DOI: 10.1007/s003590000176
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the electric organ discharge waveform of male Brachyhypopomus pinnicaudatus . II. Social effects

Abstract: Many electric fish produce sexually dimorphic electric organ discharges. Although electric organ discharges are comprised of action potentials, those of the Gymnotiform family Hypopomidae show significant plasticity in response to stress and time of day. We show here that male Brachyhypopomus pinnicaudatus (Hopkins 1991), adjusts the degree of sexual dimorphism in its electric organ discharge depending on immediate social conditions. Three to five days of isolation resulted in gradual decrease of two sexually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 0 publications
8
77
0
Order By: Relevance
“…These changes in the EODs of freeswimming fish are similar in time course and magnitude to EOD changes observed in response to 5-HT injections (Stoddard et al, 2003), social interactions (Franchina et al, 2001), and intraspecific aggression (Hagedorn and Zelick, 1989). We showed also that ACTH acts within minutes to modulate the EOD waveform of individual electrocytes in vitro, where changes in the waveform of the EOD parallel the EOD waveform changes elicited by in vivo ACTH injections and social interactions.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These changes in the EODs of freeswimming fish are similar in time course and magnitude to EOD changes observed in response to 5-HT injections (Stoddard et al, 2003), social interactions (Franchina et al, 2001), and intraspecific aggression (Hagedorn and Zelick, 1989). We showed also that ACTH acts within minutes to modulate the EOD waveform of individual electrocytes in vitro, where changes in the waveform of the EOD parallel the EOD waveform changes elicited by in vivo ACTH injections and social interactions.…”
Section: Discussionsupporting
confidence: 74%
“…ACTH is released by the action of 5-HT in the hypothalamus and pituitary (Brown, 1994), and its levels in circulation show a pronounced circadian rhythm (Nichols and Tyler, 1967). Circulating ACTH levels also are elevated by stress (for review, see Sapolsky, 2002) and social encounters (Lyons et al, 1995;Hoglund et al, 2000), consistent with our findings that stressors and social encounters modulate the EOD within minutes (Franchina et al, 2001;Stoddard et al, 2003).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Social encounters and environmental stimuli modulate the EOD waveform by altering the membrane biophysics and discharge waveforms of individual electrocytes (Ferrari et al, 1995;McAnelly and Zakon, 2000;Mills and Zakon, 1991), resulting in either a larger or smaller waveform. Social encounters modulate the EOD within minutes and large waveforms and/or rapid enhancements are associated with dominance status (Franchina et al, 2001;Hagedorn and Zelick, 1989;Stoddard et al, 2003).We have shown that intramuscular injections of 5-HT cause male B. pinnicaudatus to increase their EOD amplitude and duration akin to the waveform changes observed during male-male social interactions (Stoddard et al, 2003). These effects of 5-HT do not result from its direct action on the electrocytes, whereas melanocortin peptides do modulate the discharge waveforms of single electrocytes directly (Markham and Stoddard, 2005).…”
mentioning
confidence: 86%
“…Social encounters and environmental stimuli modulate the EOD waveform by altering the membrane biophysics and discharge waveforms of individual electrocytes (Ferrari et al, 1995;McAnelly and Zakon, 2000;Mills and Zakon, 1991), resulting in either a larger or smaller waveform. Social encounters modulate the EOD within minutes and large waveforms and/or rapid enhancements are associated with dominance status (Franchina et al, 2001;Hagedorn and Zelick, 1989;Stoddard et al, 2003).…”
Section: Introductionmentioning
confidence: 99%